Association between clinical subtypes and pregnancy outcome of cervical incompetence: a retrospective cohort study - Huiqin Xiao; Xiaofang Xing; Can Zhang; Yong Shao (BMC Pregnancy and Childbirth)
Abstract Objective To investigate the association between clinical subtypes and pregnancy outcomes of cervical incompetence. Methods The clinical data of emergency cerclage group (96 cases) were analyzed retrospectively. According to the different degree of cervical dilatation and amniotic sac protrusion during operation, the emergence cerclage group was divided into 4 subtypes: Type I(43 cases), Type II(27 cases), Type III(14 cases), and the Type IV(12 cases). Results ①Patients with type IV in the emergency cervical cerclage group had a higher frequency of late miscarriage and preterm birth when compared to the other three subtypes (type I, type II and type III) (P < 0.05);②Patients with type IV in the emergency cervical cerclage group had a lower gestational age at surgery than type I and II patients, while type III patients had a longer duration of surgery than type I and II patients, and longer length of hospital stay than type I (P < 0.05);③Patients with type IV in the emergency cervical cerclage group had a lower gestational age at termination than type I and type II patients, lower birth weight of newborns than type I and type III patients, lower term delivery rate than type I patients, and higher neonatal admission to NICU rate than type I patients (P < 0.05). Conclusion Cervical incompetence can be classified into four subtypes based on the degree of cervical dilation and amniotic sac protrusion; Transvaginal amniotic fluid reduction provides a possible surgical solution for patients with cervical incompetence type IV.